ENVIRONMENTAL SAFETY INDEX: THE CONCEPT AND EVALUATION - G. Kharlamova; V. But'kovsky (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Ecological security of the state – is a complex and multifaceted category that requires deep study. A comprehensive assessment of environmental security in terms of national security in Ukraine is not exercised. The paper summarizes the theoretical aspects of ecological safety of Ukraine and its components, contains the analysis of environmental safety indexes compiled by international organizations, including the Commission on Sustainable Development UN, the International Institute for Sustainable Development (IISD), the Scientific Committee on Problems of the Environment (SCOPE), Yale University. Analyses of such indexes as Environmental Sustainability Index, Environmental Performance Index, Human Development Index, Environmental Vulnerability Index, Enabling Environment Index had shown that despite all of them represent the level of ecological security, there is a lack of adapted for Ukraine method to assess domestic ecological situation and to compare it with global tendencies. On the basis of statistical data, a concept of evaluation of Environmental Safety Index (ESfI)of Ukraine is proposed for subsequent adequate science-based assessment of the current level of ecological situation in Ukraine in comparison with other countries. Its main feature is that it takes into account in addition to the most important environmental indicators also economic and demographic indicators as threats/risks components. The rating of more than 150 countries according to ESfI is evaluated.